CIITA-Driven MHC Class II Expressing Tumor Cells as Antigen Presenting Cell Performers: Toward the Construction of an Optimal Anti-tumor Vaccine - Accolla, Roberto S.; Ramia, Elise; Tedeschi, Alessandra; Forlani, Greta (Frontiers in Immunology, 2019)
Construction of an optimal vaccine against tumors relies on the availability of appropriate tumor-specific antigens capable to stimulate CD4+ T helper cells (TH) and CD8+ cytolytic T cells (CTL). CTL are considered the major effectors of the anti-tumor adaptive immune response as they recognize antigens presented on MHC class I (MHC-I) molecules usually expressed in all cells and thus also in tumors. However, attempts to translate in clinics vaccination protocols based only on tumor-specific MHC-I-bound peptides have resulted in very limited, if any, success. We believe failure was mostly due to inadequate triggering of the TH arm of adaptive immunity, as TH cells are necessary to trigger and maintain the proliferation of all the immune effector cells required to eliminate tumor cells. In this review, we focus on a novel strategy of anti-tumor vaccination established in our laboratory and based on the persistent expression of MHC class II (MHC-II) molecules in tumor cells. MHC-II are the restricting elements of TH recognition. They are usually not expressed in solid tumors. By genetically modifying tumor cells of distinct histological origin with the MHC-II transactivator CIITA, the physiological controller of MHC-II gene expression discovered in our laboratory, stable expression of all MHC class II genes was obtained. This resulted in tumor rejection or strong retardation of tumor growth in vivo in mice, mediated primarily by tumor-specific TH cells as assessed by both depletion and adoptive cell transfer experiments. Importantly these findings led us to apply this methodology to human settings for the purification of MHC-II-bound tumor specific peptides directly from tumor cells, specifically from hepatocarcinomas, and the construction of a multi-peptide (MHC-II and MHC-I specific) immunotherapeutic vaccine. Additionally, our approach unveiled a noticeable exception to the dogma that dendritic cells are the sole professional antigen presenting cells (APC) capable to prime naïve TH cells, because CIITA-dependent MHC-II expressing tumor cells could also perform this function. Thus, our approach has served not only to select the most appropriate tumor specific peptides to activate the key lymphocytes triggering the anti-tumor effector functions but also to increase our knowledge of intimate mechanisms governing basic immunological processes.